THE INFLUENCE OF DISCIPLINE AND WORK ENVIRONMENT ON WORK MOTIVATION AND PERFORMANCE OF MEMBERS OF THE DIRECTORATE OF DRUG RESEARCH, SOUTH KALIMANTAN REGIONAL POLICE - Henarto Yuwono; Sutrisno, Sutrisno (Sean Institute, 2020)
Performance is the embodiment of an employee's work behavior that is displayed as work performance. This indicates employee performance as a determinant of the success and survival of the organization. Without good performance, the organization will not achieve its goals. Employees need work motivation to be able to work more diligently. Discipline and a good work environment greatly affect work motivation which can have an impact on improving its performance. This study aims to determine the effect of work discipline, work environment and work motivation on employee performance. The population is all employees and members of the Directorate of Drug Investigation of the South Kalimantan Police, totaling 60 people. The researcher uses a saturated sampling technique, meaning that all populations can be used as samples in this study. Analysis of the data used is the path analysis model, because of the intervening variables in this research model. The results of this study indicate that work discipline and work environment are proven to have a significant positive effect on work motivation. Discipline, work environment and work motivation are proven to have a significant positive effect on employee performance.